TEPUNG SILASE KEPALA UDANG SEBAGAI PENGGANTI TEPUNG IKAN PADA PAKAN BENIH IKAN JELAWAT (Leptobarbus hoevenii Blkr.) - Hendry Yanto (Fakultas Perikanan dan Kelautan, Universitas Riau, 2010)
A feeding trial was conducted for 50 days to determain the optimal headshrimp silage meal as subtitues for fish meal in diets of jelawat (Leptobarbushoevenii Blkr.) The fries jelawat that had mean body weight of 1.11±0.04 gdistributed in 9 experimental treatments having 3 replicates each followingcompleted randomized design. The nine isocaloric (estimated digestibility energy360 kkal 100 g-1) and isonitrogenous (estimated 37% crude protein) diets wereprepared with 45% of fish meal and different head shrimp silage meal (0, 5, 10,15, 20, 25, 30, 35, and 40% of total fish meal). Feed was given to each treatmentat 5% of their body weight three times a day. The result showed that the proteinand lipid body, protein and lipid retention, feed consumption, feed efficiency anddaily growth rate is different significantly (P<0.05). The diet contained 30% ofhead shrimp silage meal was the highest daily gowth rate, but it wasunsignificantly (P>0.05) with the diet contained 35% of head shrimp silage meal.Jelawat fries could 35% of head shrimp silage meal in diet. The optimal level ofhead shrimp silage meal is 18,58% of total fish meal 45% in diet for optimal dailygrowth rate.